Strategi Bertahan Warung Madura di Kelurahan Pemecutan Kecamatan Denpasar Barat - Tamim, Imron Hadi; Shansa, Dewi Aprilia; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
This research focused on describing and analysing the Madura store in Pemecutan Village, West Denpasar District in building their business network and survival strategy. The method used in this research is a qualitative approach with a descriptive-explanatory type. This research was analysed with social network theory by Mark Granovetter. This study revealed that the Madura store in Pemecutan Village, West Denpasar District have been managed either by the owner directly or their employee. Even though they developed the same business, they showed respect by helping each other, practising fair competition, and maintaining cooperation to manage successful and sustainable businesses. The critical challenge faced by Madura store is competing with modern stores that are accessible to the public. Nonetheless, the person who runs the Madura store has several strategies to maintain and develop their stall to be superior to modern stores or others. Furthermore, in supporting the business sustainability of the Madura store, the manager has managed their relationship with the other Madura store managers, product suppliers, local store owners, and local people as their vital consumers.